A dinâmica hidrológica na bacia do alto curso do rio Uberabinha - Minas Gerais - Soares, Ângela Maria (2008)
This present research fetched the understanding of the landscape´s dynamic, on the basin upper course of Uberabinha river, emphasizing the water resources. The main aim of this research was to understand the superficial and subsuperficial water dynamic and its relation with the use and soil´s occupation. It´s possible that the superficial and subsuperficial water dynamics have changed because of the intense use and occupation of the soil, resulting in bad consequences for the recharge on its saturated zone. This situation interferes on the water quantity which is bound for human consumption, especially to residents of Uberlândia (MG). To understand the water dynamic , the water cycle was considered as a system, which elements are integrated in conditionated relations such as: the climate dynamic, the geological structure, the soil structure, the geomorfological features and the human actions. This survey emphasizes using the water basis as an appropiate unity for water studies , because of its open system character, that integrates several natural and social elements. On this survey, the methods from Ab´Saber (1969) and Libault (1971) were selected by their geographic character and have been adapted to the proposed aims. Libaut (1971) proposes four levels for a geographic survey and it´s a method developed for the treatment of quantified information. On the other hand, Ab´Saber believes in three levels of treatment for the research, highlighting the systematic observation and description. This survey has investigated and quantified the processes that influence on the water dynamic of the area. The collected results provided the development of the basin water balance and showed that the use and occupation of the area have caused reduction of soil permeability, and reduced the reloading of the local aquifers. The studies about the wet areas that were incorporated to the production, also showed that the human activities have changed the water local dynamics. Basing on the results, the necessity to review the use of water resources in the basin of the Upper Uberabinha was emphasized, in order to protect good water, used for the Uberlândia´s public supply and to promote the recharge´s optimization of the local and regional aquifers.